Radiation and Dose-densification of R-CHOP in Aggressive B-cell Lymphoma With Intermediate Prognosis: The UNFOLDER Study - Lorenz Thurner; Marita Ziepert; Christian Berdel; Christian Schmidt; Peter Borchmann; Dominic Kaddu-Mulindwa; Andreas Viardot; Mathias Witzens-Harig; Judith Dierlamm; Mathias Haenel; Bernd Metzner; Gerald Wulf; et al. (HemaSphere, 2023)
UNFOLDER (Unfavorable Young Low-Risk Densification of R-Chemo Regimens) is an international phase-3 trial in patients 18–60 years with aggressive B-cell lymphoma and intermediate prognosis defined by age-adjusted International Prognostic Index (aaIPI) of 0 and bulky disease (≥7.5 cm) or aaIPI of 1. In a 2 × 2 factorial design patients were randomized to 6× R-CHOP-14 or 6× R-CHOP-21 (rituximab, cyclophosphamide, doxorubicin, vincristine, and prediso[lo]ne) and to consolidation radiotherapy to extralymphatic and bulky disease or observation. Response was assessed according to the standardized response criteria published in 1999, not including F-18 fluordesoxyglucose positron emission tomography/computed tomography (FDG-PET). Primary endpoint was event-free survival (EFS). A total of 695 of 700 patients were eligible for the intention-to-treat analysis. Totally 467 patients qualified for radiotherapy of whom 305 patients were randomized to receive radiotherapy (R-CHOP-21: 155; R-CHOP-14: 150) and 162 to observation (R-CHOP-21: 81, R-CHOP-14: 81). Two hundred twenty-eight patients not qualifying for radiotherapy were randomized for R-CHOP-14 versus R-CHOP-21. After a median observation of 66 months 3-year EFS was superior in the radiotherapy-arm versus observation-arm (84% versus 68%; P = 0.0012), due to a lower rate of partial responses (PR) (2% versus 11%). PR often triggered additional treatment, mostly radiotherapy. No significant difference was observed in progression-free survival (PFS) (89% versus 81%; P = 0.22) and overall survival (OS) (93% versus 93%; P = 0.51). Comparing R-CHOP-14 and R-CHOP-21 EFS, PFS and OS were not different. Patients randomized to radiotherapy had a superior EFS, largely due to a lower PR rate requiring less additional treatment (NCT00278408, EUDRACT 2005-005218-19).